2012
DOI: 10.9790/3013-26302132
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of fibrin-chitosan composite and its in vivo studies

Abstract: Abstract--Biomaterials are used in regenerative medicine, implantable materials, controlled release carriers or scaffolds for tissue engineering. Biological dressings like fibrin glue, gelatin sheets, chitosan films, collagen is popular for quicker wound healing. These polymers when used in combination such as fibringelatin, fibrin-chitosan has shown better results, than when used alone. Thus, the present research work is concentrated on the preparation and evaluation of composite films made with chitosan-fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…For example, Balakrishnan et al [54] have reported WVTR of AD/gelatin-based films as 2686 g/m 2 /day indicating that the hydrogel can maintain a moist environment over wound bed in moderate to heavily exuding wound which would enhance epithelial cell migration during the healing process. Moreover, Devi et al [55] have reported WVTR of chitosan-fibrin composite films in the range of 2118-2383 g/m 2 /day. However, there are some reports which claim relatively higher vapour transmission rates.…”
Section: Expansion Studymentioning
confidence: 99%
“…For example, Balakrishnan et al [54] have reported WVTR of AD/gelatin-based films as 2686 g/m 2 /day indicating that the hydrogel can maintain a moist environment over wound bed in moderate to heavily exuding wound which would enhance epithelial cell migration during the healing process. Moreover, Devi et al [55] have reported WVTR of chitosan-fibrin composite films in the range of 2118-2383 g/m 2 /day. However, there are some reports which claim relatively higher vapour transmission rates.…”
Section: Expansion Studymentioning
confidence: 99%
“…The WVTR was expressed in g/mm 2 /h. 20 Young's modulus. To get the Young's modulus, the scaffolds (N = 8) were clamped at their cut ends in Universal Testing Machine (Instron Model 3365, UK).…”
Section: Physical Properties Of the Graftsmentioning
confidence: 99%